KCNN2 polymorphisms and cardiac tachyarrhythmias. Issue 29 (July 2016) - Yu, Chih-Chieh; Chia-Ti, Tsai; Chen, Pei-Lung; Wu, Cho-Kai; Chiu, Fu-Chun; Chiang, Fu-Tien; Chen, Peng-Sheng; Chen, Chi-Ling; Lin, Lian-Yu; Juang, Jyh-Ming; Ho, Li-Ting; Lai, Ling-Ping; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Potassium calcium-activated channel subfamily N member 2 (KCNN2) encodes an integral membrane protein that forms small-conductance calcium-activated potassium (SK) channels. Recent studies in animal models show that SK channels are important in atrial and ventricular repolarization and arrhythmogenesis. However, the importance of SK channels in human arrhythmia remains unclear. The purpose of the present study was to test the association between genetic polymorphism of the SK2 channel and the occurrence of cardiac tachyarrhythmias in humans. We enrolled 327 Han Chinese, including 72 with clinically significant ventricular tachyarrhythmias (VTa) who had a history of aborted sudden cardiac death (SCD) or unexplained syncope, 98 with a history of atrial fibrillation (AF), and 144 normal controls. We genotyped 12 representative tag single nucleotide polymorphisms (SNPs) across a 141-kb genetic region containing the KCNN2 gene; these captured the full haplotype information. The rs13184658 and rs10076582 variants of KCNN2 were associated with VTa in both the additive and dominant models (odds ratio [OR] 2.89, 95% confidence interval [CI] = 1.505–5.545, P  = 0.001; and OR 2.55, 95% CI = 1.428–4.566, P  = 0.002, respectively). After adjustment for potential risk factors, the association remained significant. The population attributable risks of these 2 variants of VTa were 17.3% and 10.6%, respectively. One variant (rs13184658) showed weak but significant association with AF in a dominant model (OR 1.91, CI = 1.025–3.570], P  = 0.042). There was a significant association between the KCNN2 variants and clinically significant VTa. These findings suggest an association between KCNN2 and VTa; it also appears that KCNN2 variants may be adjunctive markers for risk stratification in patients susceptible to SCD.